1991
DOI: 10.1128/iai.59.7.2351-2358.1991
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory, but not antiendotoxin, activity of lipid X is due to small amounts of contaminating N,O-acylated disaccharide-1-phosphate: in vitro and in vivo reevaluation of the biological activity of synthetic lipid X

Abstract: Lipid X, a precursor in the biosynthesis of lipid A, has been claimed to possess most of the immunostimulatory activity but none of the toxicity of endotoxin. However, recent work shows that synthetic lipid X can be contaminated with small amounts of N,O-acylated disaccharide-1-phosphate (H. Aschauer, A. Grob, J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…This phenomenon might be related to the structural compositions of compounds 406 and 401, because compound 401 differs from compound 406 by the presence of one instead of two phosphorylated glucosamine residues, so that it carries two acyl residues as compared with four in compound 406. The effect of compound 401 was further confirmed not only as the suppression of LPS-induced TNF formation (30) but also as the blocking of LPS-induced expression of monocyte procoagulant activity (29) and other LPS-related reactions (19). In our experiments, the diminished IL-6 bioactivities in the culture supernatants after the addition of compound 406 were correlated with the decreased quantities of IL-6 molecules in the supernatants, as measured by a sandwich ELISA.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This phenomenon might be related to the structural compositions of compounds 406 and 401, because compound 401 differs from compound 406 by the presence of one instead of two phosphorylated glucosamine residues, so that it carries two acyl residues as compared with four in compound 406. The effect of compound 401 was further confirmed not only as the suppression of LPS-induced TNF formation (30) but also as the blocking of LPS-induced expression of monocyte procoagulant activity (29) and other LPS-related reactions (19). In our experiments, the diminished IL-6 bioactivities in the culture supernatants after the addition of compound 406 were correlated with the decreased quantities of IL-6 molecules in the supernatants, as measured by a sandwich ELISA.…”
mentioning
confidence: 87%
“…Compound 401 (synthetic lipid X), representing a 1-phosphorylated glucosamine residue carrying two molecules of (R)-3-hydroxytetradecanoic acids, was synthesized as described previously (28). It was solubilized as described elsewhere (29). In brief, the dry substance was wetted with ethanol (10 FLl/mg of compound 401) and sonicated for 1 min in an ultrasound water bath, ensuring that the temperature was below 10°C.…”
mentioning
confidence: 99%
“…Previous reports indicated that three acyl groups on a monosaccharide backbone were required for a compound to exhibit any agonist activity. Thus, synthetic lipid X, which possesses only two acyl groups, was found to be devoid of any agonist activity, although it was found to exhibit antiendotoxin activities (16). Antiendotoxin activities have also been attributed to some disaccharide lipid A analogs (15,33).…”
Section: Discussionmentioning
confidence: 99%
“…1), it was found that lipid X retained some beneficial immunomodulatory effects of lipid A while exhibiting less toxicity (27)(28)(29). Although more recent studies have shown that the beneficial immunomodulatory effects of lipid X were due to minor disaccharide contaminants (1,16), these findings nonetheless suggested a therapeutic use for lipid A * Corresponding author. precursors either as potential enhancers of innate, nonspecific immunity in the immunocompromised individual or as immunopotentiators when incorporated in vaccines.…”
mentioning
confidence: 99%
See 1 more Smart Citation